Spanish unions and immigration. - Cachón Rodríguez, Lorenzo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The activity of the Spanish labour unions CC.OO and UGT in the presence of the phenomenon of immigration and with immigrants, started early and since then has been constant and positive in the defence of an equal treatment at work and in society at large. This position has been encouraged by a feeling of solidarity, as well as by the advisabitity of defending the coherence of labour relations. In the activity of the spanish labour unions in the face of immigration four large spheres can be distingued: 1. The individualized attention to immigrants on the part of the labour unions’: CC.OO. and UGT have both made a big organizational effort with the creation of the networks of CITES and Guiding Centres respectively. These organisms have shown themselves to be key parts, together with other private networks of attention to immigrants, in the process of nomalization of immgration in Spain; 2. The labour unions’ positions in respect of the policies which impinge on the insertion of immigrants on the labour market; 3. The actions of the labour unions in the labour markets in which the immigrants are insertd, and 4. The labour unions as employers of immigrantsand immigrants’ participation in the labour unions.A mayor contribution of labour unions to the issue of immigration (which they share with other NGOs) has been the adoption of the concern for the specific problems of the immigrants as one of their main tasks. These actions and adoption of positions fulfill an important «anticipating» function: that of preparing public opinion in general and the context of labour in particular against racism and xenophobia.